10Р∕\ ∕\ ∕\ ∕\ ∕\Р1 9 2 8 3 7 4 6 5 5 Р10 10 10 10 Р∕\ ∕\ ∕\ ∕\ Р6 4 7 3 8 2 9 1 Р 10以内减法Р 1Р1-1=0Р2Р2-1=1Р2-2=0Р3Р3-1=2Р3-2=1Р3-3=0Р4Р4-1=3Р4-2=2Р4-3=1Р4-4=0Р5Р5-1=4Р5-2=3Р5-3=2Р5-4=1Р5-5=0Р6Р6-1=5Р6-2=4Р6-3=3Р6-4=2Р6-5=1Р6-6=0Р7Р7-1=6Р7-2=5Р7-3=4Р7-4=3Р7-5=2Р7-6=1Р7-7=0Р8Р8-1=7Р8-2=6Р8-3=5Р8-4=4Р8-5=3Р8-6=2Р8-7=1Р8-8=0Р9Р9-1=8Р9-2=7Р9-3=6Р9-4=5Р9-5=4Р9-6=3Р9-7=2Р9-8=1Р9-9=0Р10-1=9Р10-2=8Р10-3=7Р10-4=6Р10-5=5Р10-6=4Р10-7=3Р10-8=2Р10-9=1Р10以内加法Р 1Р0+1=1Р2Р1+1=2Р0+2=2Р3Р2+1=3Р1+2=3Р0+3=3Р4Р3+1=4Р2+2=4Р1+3=4Р0+4=4Р5Р4+1=5Р3+2=5Р2+3=5Р1+4=5Р0+5=5Р6Р5+1=6Р4+2=6Р3+3=6Р2+4=6Р1+5=6Р0+6=6Р7Р6+1=7Р5+2=7Р4+3=7Р3+4=7Р2+5=7Р1+6=7Р0+7=7Р8Р7+1=8Р6+2=8Р5+3=8Р4+4=8Р3+5=8Р2+6=8Р1+7=8Р0+8=8Р9Р8+1=9Р7+2=9Р6+3=9Р5+4=9Р4+5=9Р3+6=9Р2+7=9Р1+8=9Р0+9=9Р9+1=10Р8+2=10Р7+3=10Р6+4=10Р5+5=10Р4+6=10Р3+7=10Р2+8=10Р1+9=10